Qādyānī maẕhab kā ʻilmī muḥāsabah : ʻajīb va g̲ẖarīb inkishāfāt va iʻtiqādāt va ijtihādāt va iftirāqāt - Barnī, Muḥammad Ilyās (SAMP early 20th-century Indian books project, 1934)
Polemic against the Ahmadiyya sect in Islam.